2019
DOI: 10.1007/s12594-019-1183-z
|View full text |Cite
|
Sign up to set email alerts
|

Stability Evaluation of Old and Unapproachable Underground Mine Workings below Surface Structures

Abstract: There are many places in the different countries of the world where working in the underground mines have been done below surface structures such as railway lines, roads, buildings, villages/residential colonies, pipelines, etc. The workings are generally old, abandoned and presently unapproachable. In some places, important delicate surface structures are installed above a portion of old abandoned underground workings. Safety of these important surface structures above old underground mine workings is a serio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Meanwhile, there will be about 15,000 sites suitable for building mineshaft-based PSH plants, with an installed capacity of approximately 1800 GW. These statistics suggest a huge market potential [30][31][32]. The PSH plant reallocates the electric generation capacity of the power system temporally and reconciles the contradictions between power generation and power consumption.…”
Section: Advantages Of a Psh Plantmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, there will be about 15,000 sites suitable for building mineshaft-based PSH plants, with an installed capacity of approximately 1800 GW. These statistics suggest a huge market potential [30][31][32]. The PSH plant reallocates the electric generation capacity of the power system temporally and reconciles the contradictions between power generation and power consumption.…”
Section: Advantages Of a Psh Plantmentioning
confidence: 99%
“…Meanwhile, there will be about 15,000 sites suitable for building mineshaftbased PSH plants, with an installed capacity of approximately 1800 GW. These statistics suggest a huge market potential [30][31][32]. The National Energy Administration has explicitly pointed out in the Pumped Storage Medium and Long-Term Development Plan 2021-2035 that ʺPSH plants fulfill multiple functions, including peak regulation, valley filling, frequency regulation, phase regulation, energy storage, backup for accidents, and black start.…”
Section: Advantages Of a Psh Plantmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, experts and scholars worldwide have performed research on rock failure and rock bridge coalescence related to mining engineering. In particular, many rock mechanics studies related to exposed abandoned roadways in working faces have been performed [5][6][7][8][9][10][11][12][13]. Zhang et al [5] proposed that due to the existence of an abandoned roadway, the working face roof exhibited further developed fracture characteristics, while the supporting stress was noticeably concentrated at the pillar.…”
Section: Introductionmentioning
confidence: 99%
“…Ma and Wang [6] used UDEC to establish a numerical model, which indicated that a bearing arch existed in the cataclastic regenerated roadway roof and that the arch rise underwent changes with an increase in the roof hanging time and with different support scenarios, and proposed an optimal roof support approach to control abandoned roadways. Kushwaha et al [7] evaluated the safety of surface structures above old underground mine workings and proposed appropriate protective measures. Zhou et al [8] analyzed the distribution law of gas on abandoned roadways and proposed surface-based radon detection to identify spontaneous combustion areas in the gobs of small coal mines.…”
Section: Introductionmentioning
confidence: 99%